Modified HEART Score Analysis in Patients with NSTEMI and STEMI - Widya Pratiwi; Sulina Yanti Wibawa; Amaliyah T. Lopa; Darmawati Rauf (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Cardiovascular disease is one of the leading causes of death. The utility of the risk score in the emergency department is for the initial examination of patients with chest pain suspected of acute coronary syndrome. HEART score was developed in the Netherlands and utilized to stratify chest pain patients and classify the risk of the patients as well as to identify the possibility of Major Adverse Cardiac Event (MACE) occurrences in 6 weeks. This study aimed to compare STEMI and NSTEMI using the modified HEART score in chest pain patients at the Integrated Heart Center (PJT) Dr. Wahidin Sudirohusodo Government Hospital, Makassar. This study used a cross-sectional approach from January 1 to March 31, 2022. The sample was drawn from patients with chest pain clinically diagnosed NSTEMI or STEMI based on the medical records containing the procedure of initial examination and HEART score risk stratification of each patient. The HEART score was found to be statistically significantly higher in STEMI (7.0 and 7.3) than in NSTEMI (6.0 and 5.6) (p<0,001). AUC 0.809 (p<0.001). The cut-off value of the HEART score can be used as a predictor of STEMI/NSTEMI. A cut-off value of 5.5 and 6.5 (alternative) were obtained from the ROC curve and can provide optimal sensitivity and specificity. The higher the score appeared on the HEART score (high risk), the higher the number of STEMI diagnoses compared to NSTEMI diagnoses. This is characterized by a significant increase of Troponin-I. Hence, the HEART score can be used as a scoring measure to predict whether the patient will be diagnosed with NSTEMI or STEMI.